Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1590/0001-3765201720160461
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity in tumor cell lines, antioxidant capacity and total phenolic, flavonoid and tannin contents of Myrciaria floribunda

Abstract: Myrciaria floribunda (H. West ex Willd.) O. Berg, Myrtaceae, is a native plant species of the Atlantic Rain Forest, from north to south of Brazil. The lyophilized ethyl acetate extract from the leaves of M. floribunda was investigated for its antiproliferative activity in tumor cell lines, antioxidant capacity and its total phenolic, flavonoid and tannin contents. Antiproliferative activity was tested in vitro against seven human cancer cells and against immortalized human skin keratinocytes line (HaCat, no ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Various studies suggest that phenolic compounds, specifically the flavonoids promoted the secondary immune response and modulate host resistance. 29,[32][33][34] Our current study showed the isolated and identified of three flavonoids 4 -6 for the first time from S. secundiflora. Also, 5-7-dihydroxy-4′-methoxyisoflavone (biochanin A) 1 and 7-hydroxy-4′methoxyisoflavone (formononetin) 2 were isolated and identified.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Various studies suggest that phenolic compounds, specifically the flavonoids promoted the secondary immune response and modulate host resistance. 29,[32][33][34] Our current study showed the isolated and identified of three flavonoids 4 -6 for the first time from S. secundiflora. Also, 5-7-dihydroxy-4′-methoxyisoflavone (biochanin A) 1 and 7-hydroxy-4′methoxyisoflavone (formononetin) 2 were isolated and identified.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, it is possible to assert that the activities of the EaE are in suitable correlation with these chemical contents, once these classes of compounds are known as potent molecules with immune modulating and radical scavenging activity. 3,33,49 The vaccinated groups showed a maximum protection of 66.6% at the 14 DPV. The protection percentage of the vaccinated and EaE-treated groups of birds at the DPV of 3, 14, 21 and 35 were 53, 87, 100, and 80%, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, TA could protect against skin tumor promotion induced by UV radiation in an in vivo study [ 207 ]. Tietbohl et al [ 208 ] have found that TA possesses anti-proliferative properties, which was tested in vitro against seven human cancer cells and immortalized skin keratinocytes. Animal studies have also shown that regular dietary consumption of TA has strongly demonstrated dose-dependent chemopreventive actions against hepatic tumor development and enhances the survival rate [ 209 , 210 , 211 ].…”
Section: Telomerase Inhibitors From Natural Productsmentioning
confidence: 99%